Analogues of the Lignan Pinoresinol as Novel Lead Compounds for P-glycoprotein (P-gp) Inhibitors - Laiolo, Jerónimo (2018)
To find novel P-gp-inhibitors, a library of pregnane X receptor (PXR) ligands and the ZINC DrugsNow library were superimposed on the P-gp inhibitor (+)-pinoresinol (1) used as a query for a three-dimensional similarity search. After determining the TanimotoCombo index of similarity with 1, eight compounds from the PXR library and two ZINC compounds were selected for biological evaluation. The P-gp inhibition study showed that compounds 7, 8, and 9 successfully increased intracellular doxorubicin (DOX) accumulation in the P-gp overexpressed Lucena 1 cells from 25, 12.5, and 6.25 μM, respectively. Among a series of analogues of 9, compounds 26–30 were shown to be active, with 26 and 27 causing a significant increase in DOX accumulation from 1.56 μM and rendering Lucena 1 sensitive to DOX from 1.56 and 0.78 μM, respectively. Molecular modeling studies showed that both compounds bind to the P-gp at transmembrane helices (TMH) 4, 5, and 6, with 27 also showing contacts with TMH 3.